2019
DOI: 10.1111/cico.12469
|View full text |Cite
|
Sign up to set email alerts
|

Relationship to Place for Older Adults in a New York City Neighborhood Undergoing Gentrification: A Discourse Analysis

Abstract: While many older adults live in neighborhoods undergoing gentrification, research rarely explores their narratives about the gentrification process and their relationships with gentrifiers. This study uses discourse analysis of ethnographic data in Queens, NY, to identify repertoires in older adults’ narratives about the meaning of place and gentrification. Five distinct repertoires emerged: (1) gentrification brings a discussion of losses; (2) talk of the insider versus outsider claim to space; (3) social con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…The study highlighted that the infrastructure project was successful in its intent to improve living conditions and increase the value of land and property in surrounding neighbourhoods but this was at the expense of a section of the community. This study highlights that decisions made to improve quality of life can have unforeseen consequences of which gentrification appears to be a well-documented example [30,31].…”
Section: Lack Of Studies To Inform Policy Makers On Trade-offs When Imentioning
confidence: 93%
“…The study highlighted that the infrastructure project was successful in its intent to improve living conditions and increase the value of land and property in surrounding neighbourhoods but this was at the expense of a section of the community. This study highlights that decisions made to improve quality of life can have unforeseen consequences of which gentrification appears to be a well-documented example [30,31].…”
Section: Lack Of Studies To Inform Policy Makers On Trade-offs When Imentioning
confidence: 93%
“… The concept requires formalising a strategy to improve ageing in place. Weil (2019) Incorporate gentrification of cities into the complexity of ageing in place. Fang et al (2016) Highlights the value of designing sustainable environments for the elderly.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Gerontological scholarship continues to examine links between housing and health that may come to the forefront in times of housing instability and subsequent transition (Fung, 2016;Versey, 2018). Whereas Smith et al (2018) found that gentrification can also bring resources to a community and perceptions of security and safety, and Weil (2019) found improvements welcomed at times, other scholars are concerned that youth-oriented development will overlook the health and social concerns of seniors (Burns, Lavoie, & Rose, 2012). In addition, older residents facing gentrification may face loss in terms of social networks and spaces, ageist hiring practices in seeking employment, and stark defunding of community resources like libraries (Finlay & Finn, 2020;Weil, 2019).…”
Section: Varied Responses To Changing Contextsmentioning
confidence: 99%
“…Whereas Smith et al (2018) found that gentrification can also bring resources to a community and perceptions of security and safety, and Weil (2019) found improvements welcomed at times, other scholars are concerned that youth-oriented development will overlook the health and social concerns of seniors (Burns, Lavoie, & Rose, 2012). In addition, older residents facing gentrification may face loss in terms of social networks and spaces, ageist hiring practices in seeking employment, and stark defunding of community resources like libraries (Finlay & Finn, 2020;Weil, 2019). Scholars are suggesting a nuanced approach to analyzing the impact of gentrification on older residents, taking into account personal and community-level assets, which must include ability to adapt to change (Weil, 2019), mobility as a key factor in social participation for older adults (Dale, Heusinger, & Wolter, 2018), and the safety and accessibility of residences, buildings, and communal spaces, andimportantly-social networks (Finlay, McCarron, Statz, & Zmora, 2019).…”
Section: Varied Responses To Changing Contextsmentioning
confidence: 99%
See 1 more Smart Citation